An inertial sensor‐based system can objectively assess diagnostic anaesthesia of the equine foot. (December 2013) - Maliye, S.; Voute, L.; Lund, D.; Marshall, J. F.
Summary: Reasons for performing study: In order for changes in lameness to be accurately and repeatably detected and recorded during diagnostic investigations, an objective measure of lameness is required. Objectives: To ascertain whether an inertial sensor‐based system can distinguish between a positive and negative response to diagnostic anaesthesia of the foot and objectively assess the effect of a positive response on the trot. Study design: Restrospective clinical study. Methods: Data obtained during lameness investigations undertaken between August 2011 and December 2012 in which either a palmar digital or abaxial sesamoid nerve block was performed were retrospectively reviewed. Response to diagnostic anaesthesia was categorised as positive (n = 14) or negative (n = 9) by one of 2 evaluators before analysis of kinematic data (i.e. blinded). Changes in maximum and minimum head difference (ΔHDMax and ΔHDMin) and change in head movement asymmetry/change in pelvic movement asymmetry (ΔHMA/PMA, measure of asymmetry) allocated to each limb were calculated. A Kruskal–Wallis one way analysis of variance on ranks was performed. Receiver operating characteristic (ROC) curves were generated for ΔHDMax, ΔHDMin and ΔHMA for the blocked limb to identify cut‐off values to distinguish positive and negative responses to the block. Results: Median ΔHDMax and ΔHDMin were significantly greater after a positive response to diagnostic anaesthesia (P<0.01). Change in head movement asymmetry allocated to the blocked limb and contralateral forelimb and ΔPMA allocated to the contralateral hindlimb were significantly greater in the positive response group (P<0.05). Change in head movement asymmetry allocated to the blocked limb and ΔHDMax and ΔHDMin are useful diagnostic tests for identifying positive response to anaesthesia (area under the curve = 0.98, 0.83 and 0.96 respectively). Conclusions: An inertial sensor‐based system can identify a positive response to diagnostic anaesthesia of the foot. Symmetry of movement allocated to the blocked limb, contralateral forelimb and contralateral hindlimb significantly improve, and head movement significantly decreases in horses with a positive response to the block. Cut‐off values for a positive response have been identified with good sensitivity and specificity. Forelimb lameness significantly affects contralateral hindlimb movement, which has implications for the investigation of multi‐limb lameness.